IMPROVING READING COMPREHENSION THROUGH JIGSAW TECHNIQUE - Pamungkas, Nurmacaca Gilang (Widya Wacana: Jurnal Ilmiah, 2018)
ABSTRACTThe aim of this research: to find out whether Jigsaw technique can increase student's reading comprehension at the eighth grade students of SMP N 3 Wonogiri in the academic year of 2017/2018; to describe the implementation of Jigsaw technique to increase student's reading comprehension at the eighth grade students of SMP N 3 Wonogiri in the academic year of 2017/2018.The researcher used classroom action research as the research method. The research was conducted from November 2017 until January 2018. In collecting data, the researcher used test and non-test. In test, the researcher used pre-test, post-test I, and post-test II. In non-test, the researcher used observation, interview, questionnaire, and documentation. Techniques that used by the researcher to analyze the data were Qualitative Data and Quantitative Data. The result of improving reading comprehension through Jigsaw technique showed thatJigsaw technique could improve the students’ reading comprehension. There was improvement of students’ reading comprehension based on the result of pre-test(63.55), post-test 1(65.78), and post-test 2 (79.74). Teaching reading comprehension by using Jigsaw technique can motivate students in learning English. It could be seen from the result of t-test between post-test I and post-test 2 was 24,38. Then t-test between post-test 1 and post-test 2 the result was higher which 2.021<24,38>2.704.  Therewere significant improvement in students’ reading comprehension. In teaching and learning process using Jigsaw technique made the students more focus, confident, and independent. They also practiced how to share their knowledge which they got. So that, they could more understand about the material.Based on the result above, it can be concluded that Jigsaw technique can improve the students’ reading comprehension. Keywords: Jigsaw Technique, Reading Comprehension, Classroom Action Research ABSTRAKTujuan dari penelitian ini: untuk mengetahui apakah teknik Jigsaw dapat meningkatkan pemahaman membaca siswa pada siswa kelas delapan SMP N 3 Wonogiri pada tahun akademik 2017/2018; untuk menggambarkan penerapan teknik Jigsaw untuk meningkatkan pemahaman membaca siswa di siswa kelas delapan SMP N 3 Wonogiri pada tahun akademik 2017 / 2018. Peneliti menggunakan penelitian tindakan kelas sebagai metode penelitian. Penelitian ini dilakukan dari November 2017 hingga Januari 2018. Dalam mengumpulkan data, peneliti menggunakan tes dan non-tes. Dalam tes, peneliti menggunakan pre-test, post-test I, dan post-test II. Dalam non-tes, peneliti menggunakan observasi, wawancara, kuesioner, dan dokumentasi. Teknik yang digunakan oleh peneliti untuk menganalisis data adalah Data Kualitatif dan Data Kuantitatif. Hasil meningkatkan pemahaman membaca melalui teknik Jigsaw menunjukkan bahwa teknik jigsaw dapat meningkatkan pemahaman membaca siswa. Ada peningkatan pemahaman membaca siswa berdasarkan hasil pre-test (63,55), post-test 1 (65,78), dan post-test 2 (79,74). Pengajaran membaca pemahaman dengan menggunakan teknik Jigsaw dapat memotivasi siswa dalam belajar bahasa Inggris. Itu bisa dilihat dari hasil uji-t antara post-test I dan post-test 2 adalah 24,38. Kemudian uji-t antara post-test 1 dan post-test 2 hasilnya lebih tinggi yaitu 2,021 <24,38> 2,704. Ada peningkatan yang signifikan dalam pemahaman membaca siswa. Dalam proses belajar mengajar menggunakan teknik Jigsaw membuat siswa lebih fokus, percaya diri, dan mandiri. Mereka juga mempraktikkan bagaimana berbagi pengetahuan yang mereka dapatkan. Sehingga, mereka dapat lebih memahami tentang materi tersebut. Berdasarkan hasil di atas, dapat disimpulkan bahwa teknik Jigsaw dapat meningkatkan pemahaman membaca siswa. Kata kunci: Teknik Jigsaw, Pemahaman Membaca, Penelitian Tindakan Kelas